The ERF transcription factor TaERF13-2B functions as a negative regulator of drought tolerance in Arabidopsis and wheat - Yu, Yang; Wang, Conglei; Wang, Jianhe; Xu, Qingfen; Zhang, Shuangxing; Song, Tianqi; Li, Guodong; Liang, Dan; Feng, Gang (Frontiers in Plant Science, 2025)
Ethylene response factors (ERFs) are transcription factors that are essential in modulating drought stress responses in plants such as Arabidopsis and rice. However, the functional role of ERF in wheat drought stress response remains unclear. We identified 33 wheat ERF genes under drought stress using transcriptomic analysis and categorized them into eight subfamilies (I–VIII). Among them, 12 drought-responsive candidate genes were upregulated, and TaERF13-2B was selected for further analysis. TaERF13-2B overexpression in Arabidopsis resulted in significantly reduced survival rates under drought conditions with decreased expression of stress-responsive and antioxidant enzyme genes, indicating that the TaERF13-2B gene elevated drought sensitivity in transgenic Arabidopsis. In wheat, overexpression of TaERF13-2B under drought stress increased malondialdehyde accumulation, decreased chlorophyll and proline levels, and reduced antioxidant enzyme activity. Furthermore, the expression of stress-responsive and antioxidant-related genes was suppressed, suggesting that TaERF13-2B negatively regulates wheat response to drought stress. The interactions between TaERF13-2B and TaCIPK9 were further confirmed using yeast two-hybrid and bimolecular fluorescence complementation. Overall, these discoveries deepen our insights into the wheat ERF family and contribute to the elucidation of the functional role of TaERF13-2B in wheat.